1994
DOI: 10.1007/bf02541548
|View full text |Cite
|
Sign up to set email alerts
|

Lignan analysis in seed oils from fourSesamum species: Comparison of different chromatographic methods

Abstract: Different chromatographic methods, thin‐layer chromatography (TLC), gas chromatography (GC), gas chromatography/mass spectrometry (GC/MS) and normal‐ and reversed‐phase high‐performance liquid chromatography (HPLC), were compared for their ability to separate the different lignans present in fourSesamum species,viz., S. indicum Linn.,S. alatum Thonn., S. radiatum Schum & Thonn. andS. angustifolium (Oliv.) Engl. The advantages and limitations of each method are discussed, and a combination of methods is sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 13 publications
1
36
2
Order By: Relevance
“…In the present study, sesamin and sesamolin were purified, from sesame oil, after saponification and preparative HPLC. The retention times for sesamin and sesamolin are similar to the retention times reported in literature (Amarowicz et al 2001;Kamal-Eldin et al 1994). The lignans were also characterized by GC-MS as given under "Materials and methods".…”
Section: Resultssupporting
confidence: 76%
“…In the present study, sesamin and sesamolin were purified, from sesame oil, after saponification and preparative HPLC. The retention times for sesamin and sesamolin are similar to the retention times reported in literature (Amarowicz et al 2001;Kamal-Eldin et al 1994). The lignans were also characterized by GC-MS as given under "Materials and methods".…”
Section: Resultssupporting
confidence: 76%
“…Manufacturers' information regarding the characteristics of the resins are reported in Table 2. -Eldin et al (1994) reported a HPLC method to determine concentrations of lignans and lignan glycosides in sesame. But the accuracy was affected by the baseline shift and these methods were not satisfactory.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with n-hexane/ chloroform (2:1) (Kamal-Eldin et al, 1994) and other solvents listed in Table 3, cyclohexane was the best choice due to its reasonable recovery and relative standard deviation.…”
Section: Analysis Optimization Of Sesamin In Sesame Oilmentioning
confidence: 98%
“…thinlayer chromatography (TLC), gas chromatography/mass spectrometry (GC/MS) and normal-and reversed-phase high-performance liquid chromatography (HPLC) [24]. The amounts of 6-episesaminol, sesamin, sesaminol, sesamol and sesamolin determined in sesame oil extract, sesame deodorizer distillate extract, and sesaminol-enriched sesame extract are provided in Tab.…”
Section: Amounts Of Antioxidant Compoundsmentioning
confidence: 99%